(untitled) (ELECTRICAL MACHINES, MATERIALS AND DRIVES — PRESENT AND TRENDS, 2026)
Mineral insulating oils used in electrical equipment are expensive, and the raw material from which they are extracted is a finite resource, so from an economic and environmental point of view, it is better to regenerate them than to replace them. This paper presents the first phase of the authors’ project to obtain an optimal solution for the regeneration of used oils from electrical equipment, bringing their parameters into line with those of type B oils in the IEC 60296:2020 standard. The paper describes the steps in the process of obtaining a composite adsorber as an innovative, economical, and environmentally friendly solution for the regeneration of used oil from electrical equipment. The results obtained from testing the used oil, both before and after the regeneration process, show an improvement in the oil’s properties, in accordance with current standards.